Hubungan Pengetahuan Ibu dan Dukungan Suami Dengan Kelengkapan Imunisasi Dasar Pada Balita Di Wilayah Kerja Puskesmas Gunung Sahilan - Ardina, Intan; Syahda, Syukrianti; Apriyanti , Fitri (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Immunization is a way to protect the body's immunity against babies and children against certain diseases, and vaccines are germs or poisons that have been weakened and inserted into the baby's or child's body. The aim of this research is to determine the relationship between husband's knowledge and support and completeness of basic immunization in the Gunung Sahilan health center work area in 2023. This research is an analytical study with a cross sectional design. The population and sample in this study were 150 mothers with toddlers aged 12-24 months and the sample was 109 mothers with toddlers using a random sampling technique. Data collection uses a questionnaire. Data analysis used univariate and bivariate analysis and Chi Square. The results of the univariate analysis showed that 35 respondents had insufficient knowledge about immunization, 65 respondents did not receive support from their husbands and 75 respondents did not receive complete immunization. The results of the chi square test showed a relationship between maternal knowledge and completeness of immunization (P value = 0.001) and husband's support and completeness of immunization (P value = 0.002). There is a significant relationship between maternal knowledge and husband's support and completeness of basic immunization for toddlers in the Gunung Sahilan health center working area in 2023.